Vimal (Iron Pyrite): A Medicinal Mineral Drug of Ayurveda - An Approach to Develop Its Mineralogical Monograph - Sharma, Vinamra (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: This communication deals with the mineralogical characterization of a mineral named Vimal (pyrite of iron) having medicinal importance in Ayurvedic system of medicine. Background: Vimal is used in the form of Bhasma for the treatment of Jirna Jwara (chronic fever), Shotha (edema), Pandu (anemia), Aruchi (anorexia), Arsha (piles), and Kamala (jaundice) and especially indicated in the diseases of Vata and Pitta Dosha dominancy. However, raw drug standardization plays a pivotal role for assuring the therapeutic potential of the final drug. Materials and Methods: The sample of Vimal was collected from local vender and authenticated by the subject experts and further analyzed through physical properties of the mineral. Results and Discussion: The results showed that Vimal is iron pyrite (iron disulfide; FeS2) with metallic luster, pale dull gold color, cubic crystal habit, and uneven fracture. Conclusion: All these physical properties of mineral iron pyrites are very well match with the acceptable characteristics of Vimal as described in Ayurvedic classic.